Niven, The Coming of the Civil War 1837-1867 - Beringer, Richard (Teaching History: A Journal of Methods, 1991)
The price of books these days has made reading lists difficult to make up for those of us who teach at colleges and universities where most students have modest budgets. Many instructors may find that this book, and others in Harlan Davidson’s American History Series, edited by John Hope Franklin, will go a long way in solving that problem.